Connecting again with elders in our community: A project to stay together during COVID-19 restrictions and beyond - Berkani, Sonia; Bukhari, Syeda; Rej, Soham; Lavin, Paola (The International Journal of Whole Person Care)

(untitled) (McGill University Library, 2021)
COVID-19 government regulations resulted in increased social isolation, risk of stress, depression, anxiety, cognitive decline, and re-hospitalization. Telehealth has been highlighted as a potential bridge for healthcare needs, especially in the COVID-19 context. In response to this need our group developed a multicultural, intergenerational, community-based psychosocial intervention. We trained more than 300 volunteers who were able to provide friendly phone support in more than 17 languages to more than 600 older adults across the Greater Montreal Area who could benefit from social connection and support to access community resources. The experience has been heartwarming and facilitating enriching life experiences for seniors, volunteers, and clinicians alike. Furthermore, some preliminary observations suggest that this intervention might have positive effects on the seniors’ mental health.